Culebras de maíz : los xatsy del depósito ritual ayuujk en Oaxacaes - Ma. Carmen Castillo Cisneros (Les Cahiers ALHIM)
The ayuujk or mixe from Oaxaca have a solid vision of the world and a strong ritual life. To perform the rituals that are part of their culture, they follow special steps under the guidance of the xëmaapyë or ritual specialist. He or she is previously consulted to indicate the amounts of bundles, corn figurines, corn powder, small tamales, cigars, candles, mezcal, tepache and poultry needed for making the offerings and the animal sacrifice. And it is women who before going to the mountain, follow a strict mathematical sequence in developing the components of the offering that will be deposited at the foot of the Catholic altar in the household and then in the mountain. Due to its particular presence on deposits made by Santa María Tlahuitoltepec ayuujk, the present work provides a description of a single element of the deposit, the xatsy (counted bundles) its shape, amount and possible meanings, following the notions of polysemy and movement.